SISTEMÁTICA y PALEOECOLOGÍA DE LA FLORA TRIÁSICA DE HILARIO-AGUA DE LOS PAJARITOS (FORMACIÓN EL ALCÁZAR), PROVINCIA DE SAN JUAN, ARGENTINA (Ameghiniana, 2014)
The systematic and paIaeoecological study of the Triassic taphoflora found in El Alcázar Formation (San Juan Province) is presented. This flora is represented by Sphenophyta, Filicopsida and Gymnospermopsida corresponding to Caytoniales, Cycadales, Ginkgoales and Coniferales groups. The following taxa are determined, described and compared: Neocalamites carrerei (Zeiller) Halle, Cladophlebis mesozoica Kurtz ex Frenguelli, C. mendozaensis (Geinitz) Frenguelli, Tranquiloxylon sp. A, Pachydermophyllum praecordillerae (Frenguelli) RetaIlack, Kurtziana cacheutensis (Kurtz) Frenguelli, Yabeiella mareyesiaca (Geinitz) Oishi, Sphenobaiera robusta (Arber) Florin, Heidiphyllum elongatum (Morris) RetaIlack y Linguifolium arctum Menéndez, which indicates a late Mesotriassic age. Furthermore, botanical affinity to Cycadales of Yabeiella, previously regarded as a gymnosperm incertae sedis, is proposed. Three different paIaeocommunities are reconstructed from the fossiliferous bed.